Somatotype analysis of elite boxing athletes compared with nonathletes for sports physiotherapy - Noh, J.-W.; Kim, J.-H.; Kim, M.-Y.; Lee, J.-U.; Lee, L.-K.; Park, B.-S.; Yang, S.-M.; Jeon, H.-J.; Lee, W.-D.; Kwak, T.-Y.; Jang, S.-H.; Lee, T.-H.; et al. (Journal of Physical Therapy Science, 2014)
The purpose of this study was to show somatotype and physical characteristic differences between elite boxing athletes and non-athletes. Methods: The somatotypes of 23 elite boxing athletes and 23 nonathletes were measured with the Heath-Carter method. The subjects were divided into four weight divisions as follows: lightweight, light middleweight, middleweight, and heavyweight class. Results: The endomorphic component values of the boxing athletes were lower than those of the nonathletes. However, the mesomorphic component values of the boxing athletes were higher than those of the nonathletes. There was no significant difference in the ectomorphic component between the two groups. The higher weight divisions tended to have higher values of height, weight, and BMI than the lower weight divisions. The higher weight divisions also tended to have higher values for the endomorphic and mesomorphic components and a lower value for the ectomorphic component than the lower weight divisions. The group of nonathletes consisted of eight endomorphs, four mesomorphs, six ectomorphs, and five central types. Among the boxing athletes, there were 16 mesomorphic, four ectomorphic, and two central types and one endomorphic type. Subdividing the athletes into 13 somatotypes resulted in five balanced mesomorphs, five endomorphic mesomorphs, five mesomorph-ectomorphs, three mesomorph-endomorphs, two mesomorphic ectomorphs, two central types, and one ectomorphic mesomorph type. Conclusion: The data from this study provides in part physical characteristics of elite boxing athletes that can be used to establish a reference for systemic study of sports physiotherapy.